The Copy Number Variation of OsMTD1 Regulates Rice Plant Architecture - Liu, Qing; Xu, Jinke; Zhu, Yunhua; Mo, Yuxing; Yao, Xue-Feng; Wang, Ruozhong; Ku, Wenzhen; Huang, Zhigang; Xia, Shitou; Tong, Jianhua; Huang, Chao; Su, Yi; et al. (Frontiers in Plant Science, 2021)
Copy number variation (CNV) may have phenotypic effects by altering the expression level of the gene(s) or regulatory element(s) contained. It is believed that CNVs play pivotal roles in controlling plant architecture and other traits in plant. However, the effects of CNV contributing to special traits remain largely unknown. Here we report a CNV involved in rice architecture by modulating tiller number and leaf angle. In the genome of Oryza sativa ssp. japonica cv. Nipponbare, we found a locus Loc_Os08g34249 is derived from a 13,002-bp tandem duplication in the nearby region of OsMTD1, a gene regulating tillering in rice. Further survey of 230 rice cultivars showed that the duplication occurred in only 13 japonica rice cultivars. Phenotypic investigation indicated that this CNV region may contribute to tiller number. Moreover, we revealed that OsMTD1 not only influences rice tiller number and leaf angle, but also represses pri-miR156f transcription in the CNV region. Intriguingly, this CNV performs function through both the dosage and position effects on OsMTD1 and pri-miR156f. Thus, our work identified a CNV and revealed a molecular regulatory basis for its effects on plant architecture, implying this CNV may possess importance and application potential in molecular breeding in rice.